A High‐Performance Bio‐Adhesive Using Hyperbranched Aminated Soybean Polysaccharide and Bio‐Based Epoxide. Issue 9 (20th March 2020) - Zhang, Yi; Chen, Mingsong; Zhang, Jieyu; Li, Jianzhang; Shi, Sheldon Q.; Gao, Qiang
Abstract: Wood adhesives fabricated from biomass can substitute formaldehyde‐based ones, reducing the consumption of fossil resources and eliminating formaldehyde pollution. In this study, a novel and sustainable water‐soluble soybean polysaccharide (WSSPS)‐based adhesive is designed. Specifically, a hyperbranched aminated polysaccharide (HBPA–g–WSSPS), as an adhesive matrix, is synthesized via grafting reaction between oxidized WSSPS and hyperbranched polyamide (HBPA). Triglycidylamine, a bio‐based epoxide cross‐linker, reacted with the HBPA–g–WSSPS to afford a cross‐linked hyperbranched network, providing strong cohesion for the adhesive. Additionally, polyacrylamide imparted an adjustable viscosity to the adhesive. The resultant WSSPS‐based adhesive enhanced the wet shear strength of plywood (1.24 MPa) by 49% compared to the E0 ‐level industrial‐use melamine‐urea‐formaldehyde (MUF) resin and by 26% compared to the industrial‐use soybean meal/polyamidoamine‐epichlorohydrin (PAE) adhesive. In addition, the adhesive has characteristics similar to those of the MUF resin, including viscosity, coating performance, hot‐pressing conditions, and dry bond strength, which are superior to those of the soybean meal/PAE adhesive. This developed polysaccharide‐based adhesive can potentially enhance various composites and can be used in industrial sectors. Abstract : A novel water‐soluble soybean polysaccharide (WSSPS)‐based adhesive is developed by hyperbranched polyamide grafting in conjunction with eco‐friendly cross‐linking. A cross‐linking hyperbranched network is formed in the adhesive to provide the adhesive with cohesive interactions, whereas the prepared hyperbranched WSSPS endowed adhesive with surface adhesive bonding. Results show that WSSPS‐based adhesive exhibits excellent water resistance, high strength, and adjustable viscosity.